Crops, crop pests and climate change – why Africa needs to be better prepared - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Ongoing investments in agriculture will not deliver for Africa until the destabilising nature of crop pests events, especially shock outbreak events, are addressed. As a result of climate change, the prevalence of crop pests will change and the frequency of shock pest events will increase, putting agricultural systems at risk. The granularity of these changes, in terms of choices by farmers, cropping systems and markets, presents a critical challenge. This submission was prepared by Julian Smith, Food and Environment Research Agency, UK (julian.smith@fera.gsi.gov.uk), with support from the CGIAR research programme on Climate Change, Agriculture and Food Security (CCAFS). The submission has received inputs from CGIAR centers and partners including, Jurgen Kroschel at the International Potato Center (CIP), and Todd Rosenstock at the World Agroforestry Centre (ICRAF).